Fostering sustainable transition: policy mix and governance evolution of China's green building sector based on large-scale text analysis (2004–2024) - Cai, Jingwen; Xie, Yingchong; Yin, Yifen; Wang, Chunning; Hu, Haoqian (Frontiers in Sustainability, 2025)
To systematically reveal the policy efforts and evolutionary logic behind China's sustainable transition in the building sector, this study conducts a large-scale text analysis of 2,945 central and local policy documents from 2004 to 2024, integrating non-negative matrix factorization (NMF) topic modeling, policy instrument coding, and multi-level governance (MLG) comparison. The findings indicate that the policy agenda for green building in China has followed a clear trajectory from “foundation-laying” (macro-planning and standard-setting) to “implementation-deepening” (certification management and process supervision), closely linked with national sustainable development strategies. The policy mix is characterized by a “regulation-dominant” approach, with mandatory instruments at its core, supplemented by organizational and capacity-building tools. Incentive-based instruments are applied periodically, while informational and system-changing instruments remain relatively underutilized. In the multi-level governance structure, the central government focuses on strategic guidance, whereas local governments exhibit significant strategic adaptation based on regional heterogeneity. This study provides empirical evidence and theoretical insights into how China utilizes dynamic policy mixes and evolving governance to foster a sustainable transition in a specific sector, offering practical implications for optimizing future policy design to better cultivate endogenous market drivers.